2001
DOI: 10.1152/ajpregu.2001.280.6.r1606
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of REM sleep during extraocular light exposure in humans

Abstract: This study examined the effects on sleep of light administered to an extraocular site. A 3-h photic stimulus was applied to the popliteal region during sleep in 14 human subjects. Each subject also underwent a control stimulus condition during a separate laboratory session. The proportion of rapid eye movement (REM) sleep during the 3-h light administration session increased by an average of 31% relative to the control condition. The frequency but not the duration of REM episodes was altered during light expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Up until now, the only new positive result on the extraocular photosensitivity of the human brain was from the group that reported those effects originally. In the new study, Murphy and Campbell (2001) exposed sleeping subjects to extraocular light and showed an enhancement of REM sleep. No other group has replicated this study up until now.…”
Section: Discussionmentioning
confidence: 97%
“…Up until now, the only new positive result on the extraocular photosensitivity of the human brain was from the group that reported those effects originally. In the new study, Murphy and Campbell (2001) exposed sleeping subjects to extraocular light and showed an enhancement of REM sleep. No other group has replicated this study up until now.…”
Section: Discussionmentioning
confidence: 97%
“…Although small, the present data suggest that extraocular light exposure may have an acute negative effect on sleep. By contrast, Murphy and Campbell (2001) reported no evidence for increased wakefulness with the effects of extraocular light exposure on sleep limited to increased REM. It is possible that the increased wakefulness observed in the present study may be explained by the switching between the fan and BiliBlanket Plus housing units and any concomitant change in stimuli at the start of the extraocular light exposure period, such as noise.…”
Section: Placebomentioning
confidence: 96%
“…If similar effects occur with extraocular light exposure, then this may limit its clinical application. At present, our understanding of the effects of extraocular light exposure on sleep is restricted to one study by Murphy and Campbell (2001). Murphy and Campbell examined the effect of a 3-h pulse of light behind each knee on sleep in 14 subjects.…”
mentioning
confidence: 99%